Diagnostic challenges in children with celiac disease. A five-year experience with new guidelines in a General Pediatrics Department - Daniela Pop; Radu Samuel Pop; Cristina Nicoleta Schnell; Valentina Tarau-Sas; Edita Gabriela Ichim; Paraschiva Chereches-Panta; Daniela Iacob; Dan Gheban; Sorin Claudiu Man; Dorin Farcau (Amaltea Medical Publishing House, 2023)
Background. The clinical characteristics of patients with celiac disease cover a wide range of signs and symptoms. Our study aimed to describe the main clinical features and investigations performed on our celiac patients diagnosed in the past five years. Material and methods. We collected data from medical records of patients aged 0 to 18 years diagnosed with celiac disease. We included in the analysis patients newly diagnosed with celiac disease, in our department, between January 2017 and August 2022. Results. In this period, 30 children were diagnosed with celiac disease in our general pediatrics department. The mean age at diagnosis ± standard deviation was 6.3±4.2 years (median age=4.3 years). The period between onset of symptoms ranged between 3 months to 5 years (median=6 months). Twenty children (66%) had features of classical celiac disease. Thirteen/30 patients (43.3%) were found to have iron deficiency anemia at diagnosis. In 23/30 (76%) of the children, the values of the IgA-TGA were more than 10 times the upper limit of the normal values. Nineteen children were diagnosed between 2017 and 2019. Fifteen of these 19 patients (79%) were diagnosed based on positive levels of antibodies and duodenal biopsy samples showing Marsh 2 or 3 features, and 4/19 (21%) based on positive IgA-TGA and AEM and a genetic test showing HLA DQ2 and/or DQ8. Conclusions. Classical celiac disease remains the predominant phenotype in our patients. Adherence to new guidelines allowed in the past 2 years a diagnosis without histological examination of biopsy fragments in most of the patients.